Association between breastfeeding in the first hour of life and exclusive breastfeeding at 3 and 6 months - Lorencini Santos, Isabela; Mascarello, Keila (Guará Journal, 2025)
Breastfeeding within the first hour of life is recommended by the World Health Organization as a crucial tool for promoting, protecting, and supporting newborn breastfeeding. In light of the importance of promoting breastfeeding, providing qualified nursing care, and training professionals for adequate breastfeeding support, the extension project “Bebê que mama: orientações e cuidados em amamentação” was developed. This study aims to estimate the association between the mode of delivery and breastfeeding within the first hour of life, as well as exclusive breastfeeding at 3 and 6 months, and to promote practical and educational interventions that can be applied in daily breastfeeding support. This is a prospective cohort study, where 112 newborns were followed at birth, and at 3 and 6 months of age. 32.14% of babies were not breastfed within the first hour of life, with most of these being born via cesarean section. Vaginal delivery and breastfeeding within the first hour of life were associated with higher prevalence rates of exclusive breastfeeding at 3 and 6 months. Breastfeeding within the first hour of life was hindered by the mode of delivery, and the lack of early breastfeeding negatively affected the duration of exclusive breastfeeding. This highlights the importance of professional intervention on this key determinant of breastfeeding success.